Women Leaders in the Ancient Synagogue - Brooten, Bernadette J. (Book collections on Project MUSE., 2020)
This book argues that women served as leaders in a number of synagogues during the Roman and Byzantine periods. The evidence for this consists of nineteen Greek and Latin inscriptions in which women bear the titles "head of the synagogue," "leader," "elder," "mother of the synagogue" and "priestess." These inscriptions range in date from 27 B.C.E. to perhaps the sixth century C.E. and in provenance from Italy to Asia Minor, Egypt and Palestine. While new discoveries make this a growing corpus of material, a number of the inscriptions have been known to scholars for some time. The book contains a new preface by the author.